SISTEM INFORMASI PERMINTAAN PEMBELIAN BAHAN BAKU DAN ATK PADA PT MADA WIKRI TUNGGAL MENGGUNAKAN LARAVEL 9 - Trisanto, Dedy; Husna, Nahdah Salma; Rismawati, Nofita; Mulya, Muhamad Femy (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
PT Mada Wikri Tunggal is an automotive industrial company in the field of metal and plastic components that produces goods in the form of spare parts for two-wheeled (2) and four-wheeled (4) vehicles. The purchasing department at PT Mada Wikri Tunggal is responsible for the availability of goods needed by other departments according to the time required. Before carrying out the process of purchasing raw materials and stationery, the purchasing department must have a purchase request form for raw materials or stationery originating from the department concerned. In the process of purchasing raw materials and stationery, several problems were found, such as purchasing the same goods in one purchase request, and also the loss of the purchase request form which could hamper the process of purchasing raw materials or stationery. Therefore, it is necessary to design an information system application for purchasing requests for raw materials and stationery by depicting it using UML diagrams, ERD, and interface design as well as web-based integrated development using the Laravel framework and applying the waterfall method. The existence of an information system for purchasing requests for raw materials and stationery can minimize errors in purchasing raw materials and stationery in the purchasing department at PT Mada Wikri Tunggal so that there will be no duplication of the same purchase in one purchase request and it will not take a long time to send purchase orders. to suppliers.